Effects of rehabilitation with complete dentures on bite force and electromyography of jaw and neck muscles and the correlation with occlusal vertical dimension - Pereira de Caxias, Fernanda [UNESP]; Leal Túrcio, Karina Helga [UNESP]; de Moraes Melo Neto, Clóvis Lamartine [UNESP]; Florencio de Athayde, Flávia Regina [UNESP]; Coelho Goiato, Marcelo [UNESP]; Micheline dos Santos, Daniela [UNESP] (Springer Nature, 2021)
Objectives: The purpose of this study was to assess the effects of oral rehabilitation with complete dentures on bite force and electromyography of the suprahyoid and sternocleidomastoid muscles, and their correlation with occlusal vertical dimension (OVD). The research questions were “What are the effects of rehabilitation with complete dentures on bite force and electromyography of suprahyoid and sternocleidomastoid muscles, and how are they correlated with OVD?” Materials and methods: Patients who are wearers of unsatisfactory removable complete dentures were attended in three sessions (T0, T1, and T2). At T0, while the patients still wore the old dentures, they were submitted to bite force and surface electromyographic exams of the suprahyoid and sternocleidomastoid muscles. These exams were repeated, and the OVD was measured while the patients wore their old and new prostheses, 30 days after insertion of the new prosthesis (T1). The exams were repeated 100 days after the insertion of the new prosthesis (T2). The data were submitted to the Shapiro-Wilk normality test, analysis of variance (ANOVA), and Pearson correlation and linear regression, all with 5% significance. Results: Fifteen patients participated in the study. No statistically significant difference was observed for bite force or electromyography in T0, T1, or T2. However, the correlation and regression tests showed important interactions between the OVD and maximum voluntary occlusal bite force, as well as the OVD and electromyography during deglutition for the suprahyoid muscles. Conclusion: Rehabilitation did not impact bite force nor the activity of the assessed muscles (electromyography). On the other hand, OVD was shown to be an important factor for bite force, and deglutition of water after rehabilitation. Clinical relevance: This study shows what are the influences of rehabilitation on oral functions and reinforces the importance of corrected reestablishment of OVD because it has been found to be an important factor for bite force and electromyography during deglutition.
Keywords: Bite force; Electromyography; Mouth rehabilitation; Skeletal muscle; Stomatognathic system; Vertical dimension